2014
DOI: 10.5194/isprsannals-ii-8-45-2014
|View full text |Cite
|
Sign up to set email alerts
|

Species Discrimination of Mangroves using Derivative Spectral Analysis

Abstract: ABSTRACT:Mangroves are salt tolerant trees or shrubs commonly seen in mudflats of intertidal regions of tropical and subtropical coastlines. Recent advances in field spectroscopic techniques enabled the species level discrimination among closely related vegetation types. In this study we have analysed the laboratory spectroscopy data collected from eight species of Rhizophoraceaea family of mangroves. The spectral data ranges between the wavelength of 350 nm and 2500 nm at a very narrow bandwidth of 1 nm. Prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This influence has been effectively mitigated by employing derivative spectra (Zhang et al. 2006 ; Prasad and Gnanappazham 2014 ). First-order derivative spectra (dR) reveal the peak characteristics of the spectrum, reflecting waveform changes caused by the absorption of light by chlorophyll and other substances in plants (Becker et al.…”
Section: Methodsmentioning
confidence: 99%
“…This influence has been effectively mitigated by employing derivative spectra (Zhang et al. 2006 ; Prasad and Gnanappazham 2014 ). First-order derivative spectra (dR) reveal the peak characteristics of the spectrum, reflecting waveform changes caused by the absorption of light by chlorophyll and other substances in plants (Becker et al.…”
Section: Methodsmentioning
confidence: 99%
“…Derivative spectra are commonly employed in hyperspectral investigations of vegetation [45], which can effectively reduce the influence of illumination variations, and eliminate the background signal and systematic errors. Previous studies have reported that the derivative analysis can further enhance the ability of the spectral data to identify tree species [46], and has been developed for mangrove species classification [47]. First-order derivative spectra can reflect the waveform changes caused by the absorption of the light by chlorophyll and other substances in plants, and reveal the peak characteristics of the spectrum [48].…”
Section: Data Transformationmentioning
confidence: 99%